Reindeer pastoralism in Sweden 1550-1950 - Lundmark, Lennart (Rangifer, 2007)
In the middle of the 16th century we get the first opportunity to a more detailed knowledge of reindeerpastoralism in Sweden. At that time the Sami lived in a hunter-gatherer economy. A family had in average about 10-20 domesticated reindeer, mainly used for transport. They could also be milked and used as decoys when hunting wild reindeer. During late 16th century the Swedish state and merchants bought large amounts of fur from the Sami. The common payment was butter and flour. This created a new prosperity, which lead to a considerable increase in population in Swedish Lapland. The population became too large for a hunter-gatherer economy. A crisis in early 17th century was the starting point for the transition to a large-scale nomadic reindeer pastoralism. Up to the middle of the 18th century intensive reindeer pastoralism was successful. But the pastoralism became gradually too intensive and diseases started to spread when the herds were kept too densely crowded for milking in summertime. During the first decades of the 19th century reindeer pastoralism in Sweden went through a major crisis. The number of reindeer herding mountain-Sami decreased considerably, mainly because they went to live permanently along the Norwegian coastline. Intensive reindeer pastoralism started to give way for extensive herding towards the end of the 19th century. In the north of Sweden influences from the Kautokeino Sami were an important factor, in the south extensive reindeer herding started to expand when the market for meat came closer to the Sami. During the 1920s the milking of reindeer ceased in Sweden, except in a few families. At that time Sami families from the north had been removed southwards. They further demonstrated the superiority of extensive herding to the Sami in mid- and southern Lapland. Reindeer pastoralism is basically a system of interaction between man and animal, but it has been heavily influenced by market forces and state intervention during hundreds of years. To a large extent these long-term external ...